Anxiety and depression in family caregivers of hemodialysis patients: Incidence, risk factors, and correlation - Akbar Zulkifli Osman; Eska Agustin Putri Susanti; Reza Ishak Estiko; Meiza Fadhila Azzahra; Andika Danendra Widyadhana (JKKI (Jurnal Kedokteran dan Kesehatan Indonesia), 2023)
Background: Chronic kidney disease (CKD) imposes a significant global burden, with diabetes and hypertension being major contributors. In the severe stage, CKD patients require long-term hemodialysis (HD) treatment and rely on family caregivers for support. Caregivers often experience mental health challenges, including anxiety and depression, which can impact their quality of life and patient outcomes. Objective: This study aimed to identify the anxiety and depression incidence in HD family caregivers at Soehadi Prijonegoro Regional Public Hospital (SPRPH), identify the risk factors associated with these conditions, and investigate the relationship between anxiety and depression Methods: A cross-sectional analysis was carried out at the Hemodialysis Department from November 2022 to February 2023. Caregivers accompanying CKD patients undergoing HD participated voluntarily. Anxiety and depression levels were evaluated using the Hamilton Anxiety Rating Scale (HAM-A) and Hamilton Depression Rating Scale (HAM-D). Results: Out of 106 participants, 66% were female. Most caregivers (99%) experienced anxiety, with 91% classified as mild and 8% as mild to moderate. Depression was reported by 42%, with 2% experiencing mild to moderate symptoms. Spearman’s analysis revealed a significant correlation between anxiety and depression (p=0.000). No specific caregiver characteristics were found to be associated with anxiety or depression. Conclusion: Family caregivers of HD patients demonstrated a high incidence of anxiety and a lower prevalence of depression. Anxiety levels were correlated with depression levels. We did not identify specific risk factors for these mental health conditions among caregivers. These findings emphasize the need for mental health screening and appropriate management to improve the quality of life for HD family caregivers.